Revictimization in the Journalism Discourses of El Tiempo and Q’hubo on Femicides - Cortés-Martínez, Carlos A.; Salazar Baquero, Carol Andrea (Estudios sobre el Mensaje Periodístico, 2023)
This qualitative article, critically, empirically, comparatively and longitudinally, describes the shared and independent discourses of the newspapers El Tiempo and Q’hubo on femicides, from July 2015, date when Colombia ruled those cases as crimes, until July of 2022. A combination between the tenets of Critical Discourse Analysis from feminists perspectives and Critical Discourse Analysis focused on journalism allowed the study 324 news articles on femicides in Bogotá. Findings show that not all revictimization discourses towards women were simultaneously present on the chosen outlets, that El Tiempo respected victims because the newspaper neither minimized women to foster pity nor referred to them with derogative adjectives, while Q’hubo’s representations characterized for constant descriptions of women’s physical appearance, and that both publications lacked precision in the usage of the concept of femicides.